Ensino de pronúncia: visões de professores de inglês em três contextos diferentes de ensino - Swiech, Rafael (2015)
This research aims to analyze how English teachers see their identity and at the same time addresses the pronunciation in English teaching. Based on the principles of English as a lingua franca, this piece of work points out the degree of knowledge on the matter, as well as the usage of this approach. The research had language center, Regular Schooling and University Education teachers, in order to draw a parallel comparison of the three groups. The methodology used for the collection and analysis of data is quantitative and qualitative. The theoretical framework authors are mainly of English pronunciation teaching: Albini and Gomes (2014), Becker (2014), Crystal (2010), Kenworthy (1994), Jenkins (2000), among others. As a result, one can see that despite the common discourse of teachers defending learning based on the construction of intelligibility there are still many beliefs, prejudices and lack of knowledge of the English as a lingua franca, especially among teachers of language centers. Therefore, it is understood that the teaching process of English is not common to all segments it happens and that it is a duty of the Educational Academy to develop more integrative researches approaching subjects such as English as a lingua franca.